2013
DOI: 10.7314/apjcp.2013.14.9.5127
|View full text |Cite
|
Sign up to set email alerts
|

Can Capecitabine be used Instead of Concurrent Bolus 5-FU in Postoperative Chemoradiotherapy for Gastric Adenocarcinoma?

Abstract: Background: 5-fluoro-uracil (FU) is a common agent in postoperative chemoradiation in gastric adenocarcinoma. However, FU is not well tolerated in a significant proportion of patients. Capecitabine (CA) is an orally administered fluoropyrimidine carbamate which is preferentially converted to active 5-FU and is one of the agents used instead of FU in such cases. We compared the toxicity, local and distant control and survival rates with FU or oral CA during the course of concurrent radiotherapy to assess the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The literature has revealed that 5-Fu wrapped with adjuvant has a good effect in intraperitoneal chemotherapy of gastric cancer [ 17 ]. Besides, the efficacy of 5-Fu is positively associated with its action duration [ 18 , 19 ]. In general, the release time of 5-Fu wrapped with adjuvant does not exceed 1 day, whereas that of sustained-release 5-Fu implantation lasts more than 10 days, which overcomes the disadvantage of conventional chemotherapeutic drugs with a short action duration [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature has revealed that 5-Fu wrapped with adjuvant has a good effect in intraperitoneal chemotherapy of gastric cancer [ 17 ]. Besides, the efficacy of 5-Fu is positively associated with its action duration [ 18 , 19 ]. In general, the release time of 5-Fu wrapped with adjuvant does not exceed 1 day, whereas that of sustained-release 5-Fu implantation lasts more than 10 days, which overcomes the disadvantage of conventional chemotherapeutic drugs with a short action duration [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature has revealed that 5-Fu wrapped with adjuvant has a good effect in intraperitoneal chemotherapy of gastric cancer (Yoshimura et al, 2011). Besides, the efficacy of 5-Fu is positively associated with its action duration (Hu et al, 2013;Yoney et al, 2013). In general, the release time of 5-Fu wrapped with adjuvant is not more than 1 day, whereas that of sustained-release 5-Fu implantation is more than 10 days, which overcomes the disadvantage of conventional chemotherapeutic drugs with short action duration Zhang et al, 2013) .…”
Section: Discussionmentioning
confidence: 99%
“…As the DCF regimen has been associated with high toxicity profiles, several clinical trials have tested modifications of the DCF regimen utilizing capecitabine and dose modifications , with the aim of reducing toxicity and improving tolerability (Koizumi et al, 2003;Ozdemir et al, 2010;Kang et al, 2011;Kos et al, 2011;Polyzos et al, 2012;Alici et al, 2013). In addition, substitution of capecitabine, an orally administered fluoropyrimidine, for the continuous infusion of fluorouracil prevents the inconvenience of additional cost and morbidity with no negative impact on efficacy and safety in both early and advanced gastric cancer (Hong et al, 2004;Kang et al, 2009: Yoney andIsikli, 2013). Kang et al (2009) compared the combination of cisplatin and capecitabine (CX) with CF in AGC patients in the first-line setting in ML17032 trial.…”
Section: Introductionmentioning
confidence: 99%